Comparative performances of hilly chicken and naked neck hilly chicken at Naikhongchari hilly areas of Bangladesh (Asian Journal of Medical and Biological Research, 2016)
A total of 115 hilly chickens (92 female and 23 males) and 35 naked neck hilly Chickens (28 females and 7 males) were reared in open sided poultry house for 10 months period to compare their productive and reproductive performances. The mean body weights of adult female and male hilly birds and naked neck hilly birds were 2244, 2005 and 2664, 2576 g respectively. The age at first egg of both type of birds were 147 and 159 days respectively and hen-day egg production were 27±1.4 and 35±3.3 respectively. The average egg weight was 41±4 and 38±3.6 g respectively. Both type of bird per day average feed consumption were 97.61±11 and 102±22 g and mortality were 15.56±3.7 and 11.42±2.7 percent respectively. The average hatchability percentage performed by 14 broody hens reared on litter floor was 67.5±10 and 57±22 percent respectively. The average hatching egg weight and chick weight were 47.28±3, 41.48±1 and 31.4±3, 29.6±4 g respectively. The body weight of growing hilly bird and Naked Neck hilly bird after eleven weeks of age were 727.3±17.4 and 645±97.6g, respectively and Feed conversion ratios (FCR) were 3.39 and 3.34 respectively. It was concluded that Hilly chicken improved by body weight than previous year and both feathered and Naked Neck Hilly chicken given an indication of meat type native chicken and required to reproduce to have large stock for undertaking conservation and further improvement programme.Asian J. Med. Biol. Res. June 2016, 2(2): 348-351